Variants within the COL5A1 gene are associated with Achilles tendinopathy in two populations. Issue 5 (28th April 2008) - September, A V; Cook, J; Handley, C J; van der Merwe, L; Schwellnus, M P; Collins, M
Abstract : Objectives: A COL5A1 gene variant was shown to be associated with chronic Achilles tendinopathy in a South African population. The aim of this case–control genetic association study was to investigate the Bst UI and Dpn II restriction fragment length polymorphisms (RFLP) in a second population from Australia and to identify a predisposing haplotype for Achilles tendinopathy in both populations. Methods: 85 Australian and 93 South African patients with tendinopathy, as well as 210 Australian and 132 white South African control subjects were genotyped for the Bst UI ( rs 12722) and Dpn II ( rs 13946) RFLP, as well as markers rs 10858286, rs 3196378, rs 11103544, rs 4504708 and rs 3128575. Results: The BstU I RFLP (p<0.001) and marker rs 3196378 (p = 0.016) were associated with chronic Achilles tendinopathy in Australian subjects. Individuals within both populations with a CC genotype for the BstU I RFLP had a significantly decreased risk of developing tendinopathy versus any other genotypes (Australian odds ratio 0.42, 95% CI 0.20 to 0.86, p = 0.017). The TC inferred haplotype ( rs 12722, rs 3196378) was found to be overrepresented (global p = 0.008) in the South African tendinopathy group compared with all other haplotypes. Conclusion: The Bst UI RFLP is associated with chronic Achilles tendinopathy in a second population and a region within the COL5A1 3′ untranslated region may predispose individuals to an increased risk of developing chronic Achilles tendinopathy.